Pemberdayaan Masyarakat Petani Melalui Program Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) di Desa Beru-Beru Kecamatan Kalukku Kabupaten Mamuju - Hidayat, Nur Azikin; Ibnu, Anthony (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
The increasing number of people have raised concerns over the state of "food insecurity" in the future, for it is to meet the food needs of West Sulawesi province through the Department of Agriculture and Livestock program Integrated Management Field School (SLPTT). This observation titled "COMMUNITY EMPOWERMENT THROUGH FARMERS FIELD SCHOOL PROGRAM MANAGEMENT INTEGRATED PLANT (SL-PTT) IN VILLAGE BERU BERU SUB-DISTRICT KALUKKU Production". Problems encountered in the implementation of this program are the model adopted in the implementation of the program, the factors that affect production and farm income, and the pattern of development. This observation aims to determine how the implementation of the Programmed of Integrated Crop Management Field School (SLPTT) in the village of Beru-Beru, as well as to find out what the inhibiting factors in the implementation of this program in the field. This observation was held in the Village District of Kalukku Beru Beru-Mamuju, using a descriptive method with a qualitative approach. To get the data and facts, in addition to leaning on what the author met through field observations, then features interviews and secondary data sources. Based on the results of the analysis the author proposes, in the village of Program implementation, SLPTT Beru-Beru has been successfully implemented, which in practice has been able to achieve the targets and objectives that have been planned and involve the participation of farmers to improve agricultural yields abundantly. Obstacles encountered in the implementation of this program, include no reciprocity from the government for farmer groups who implement programs SLPTT rice, lack of farmer group administrator attempts to make the counseling group meetings, different levels of soil fertility, Distinct economic capabilities, the use of agricultural technologies are not yet ready, the limited budget allocated,.